Efficacy and safety of immune checkpoint inhibitors in elderly patients (≥70 years) with squamous cell carcinoma of the head and neck. (November 2021) - Saleh, Khalil; Auperin, Anne; Martin, Nicolas; Borcoman, Edith; Torossian, Nouritza; Iacob, Mariana; Ferrand, Francois-Regis; Khalife, Nadine; Baste, Neus; Guigay, Joel; Le Tourneau, Christophe; Daste, Amaury; et al.
Abstract: Background: Recent meta-analysis showed that immune checkpoint inhibitors (ICIs) have comparable activity between younger and older patients. However, little is known about efficacy and safety of ICI in elderly patients with relapsed/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). The aim of this study is to compare the efficacy of ICI for patients aged ≥70 y to that for younger patients, while taking into account potential confounding factors. Methods: A retrospective study was conducted at four hospitals in France. Patients treated with ICI for R/M SCCHN between September 2014 and December 2018 were eligible. Patients' charts were reviewed for clinical and radiological data as well as oncologic outcomes. Results: We included 226 patients, of whom 67 were aged ≥70 years. Objective response rate (ORR), median overall survival (OS) and median progression-free survival (PFS) were 23%, 9.7 months and 2.7 months, respectively, for elderly patients, compared to 13%, 8.7 months and 1.9 months for younger patients (respective p-values: 0.071, 0.87 and 0.21). After adjustment for performance status, site of progression, number of ICI drugs, time between initial diagnosis and ICI start and number of previous lines, age ≥70 years was significantly associated with a better PFS (hazard ratio [HR], 0.66; p = 0.021) but not OS (HR, 0.91; p = 0.59). Grade 3-5 adverse events (AEs) occurred in 15% of patients aged ≥70 years and in 8% of younger patients (p = 0.13). Conclusion: Patients aged ≥70 years with R/M SCCHN may respond to ICI similarly as younger patients in terms of ORR, OS and PFS, while maintaining comparable rate of AEs. Highlights: The ORR in elderly patients was 23% versus 13% in younger patients. Elderly patients have OS comparable to that of younger patients (9.7 versus 8.7 months). Elderly patients have PFS comparable to that of younger patients (1.9 versus 2.7 months). Elderly patients have rate of adverse events comparable to that of younger patients.